2007
DOI: 10.3748/wjg.v13.i10.1561
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the MEK1/2 and AKT pathways in CXCL12/CXCR4 induced cholangiocarcinoma cell invasion

Abstract: AIM:To evaluate the expression of C-X-C motif chemokine receptor 4 (CXCR4) and its signaling cascades, which were previously identified as a key factor for cancer cell progression and metastasis, in cholangiocarcinoma cell lines. METHODS:The expression of CXCR4 and its signaling cascades were determined in the cholangiocarcinoma cell lines (RMCCA1 and KKU100) by Western blotting. The invasion assays and the detection of actin polymerization were tested in these cholangiocarcinoma cells treated with CXC chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
43
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 25 publications
11
43
0
1
Order By: Relevance
“…Blocking CXCL12/CXCR4 interaction or inhibiting downstream intracellular signaling pathway may be useful for cancer therapy (4). We found that CXCL12 stimulation activated PI3K/Akt/mTOR signaling cascade in gastric cancer MKN-45 cells, which is consistent with the previous report, where phosphorylated Akt was utilized as an indirect marker for the activation of PI3K (7,(22)(23)(24)(25). By employing CHO-K1 cells stably expressing pEGFP-C1-Grp1-PH fusion protein, we demonstrated that CXCL12 stimulation resulted in generation of PtdIns(3,4,5)P 3 and the translocation of protein contained PH domain to cellular membrane, providing direct evidence that CXCL12 activated PI3K.…”
Section: Discussionsupporting
confidence: 93%
“…Blocking CXCL12/CXCR4 interaction or inhibiting downstream intracellular signaling pathway may be useful for cancer therapy (4). We found that CXCL12 stimulation activated PI3K/Akt/mTOR signaling cascade in gastric cancer MKN-45 cells, which is consistent with the previous report, where phosphorylated Akt was utilized as an indirect marker for the activation of PI3K (7,(22)(23)(24)(25). By employing CHO-K1 cells stably expressing pEGFP-C1-Grp1-PH fusion protein, we demonstrated that CXCL12 stimulation resulted in generation of PtdIns(3,4,5)P 3 and the translocation of protein contained PH domain to cellular membrane, providing direct evidence that CXCL12 activated PI3K.…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, this is the first study to demonstrate the signal transduction pathways of bFGF/FGFR in cholangiocarcinoma cells. Previous studies also showed that activation of c-met, a hepatocyte growth factor receptor, or CXCR4 was capable of inducing cholangiocarcinoma cell migration via the activation of the MEK1/2 signaling pathway (20,21). Therefore, we suggest that MEK1/2 is the central signaling pathway for the control of cholangiocarcinoma cell migration.…”
Section: Discussionsupporting
confidence: 61%
“…It is widely accepted that inactivating the PI3K/AKT pathway is one of the mechanisms through which kaempferol exerts its biochemical effects [17,40,41]. Furthermore, previous studies have reported that the PI3K/AKT pathway is a major survival pathway involved in the apoptosis and invasion of CCA [42,43]. Our data showed that kaempferol suppressed the expression levels of PI3K P110α, p-AKT, and p-p65, with no obvious changes in the total AKT protein level.…”
Section: Discussionsupporting
confidence: 48%